The impact of dyadic processes and financial management roles on farm couples - Archuleta, Kristy L. (Kansas State University, 2008)
This study was designed to investigate the link between marital quality and financial management roles by gaining insight into the relationship processes of farm couples. Fifty-five married individuals who identified living in a rural or farm location comprised the sample. Each participant completed a paper-pencil survey that included assessment of demographic variables, financial management role involvement, satisfaction with financial management roles, financial satisfaction, and marital satisfaction. Results indicated that respondents of this study were more likely than their spouses to hold primary responsibility for financial management roles and were moderately satisfied with their role involvement. This finding indicated that couples may specialize in taking on the financial management roles they play, rather than working together jointly. Secondly, a new scale emerged, based on Gottman's Sound Relationship House Scales, and was entitled "Shared Goals & Values," utilizing a factor analysis. This scale assessed the meaning of money, financial goals, views about autonomy, and hopes and aspirations within the couple relationship. The Shared Goals & Values scale was found to be a factor influencing both marital satisfaction and financial satisfaction. This finding indicated that the way a couple views money does have impact on marital satisfaction and financial satisfaction. Finally, evidence was found that having shared views about roles within the relationship was more of a predicting factor for financial satisfaction than how a couple communicated during conflict. In regards to a couple's perceived financial satisfaction, having similar perceptions about relationship roles, shared views about money, financial management role satisfaction and increased household income were the important predicting factors. Sharing similar views about money and support for goals in one's life, and household income were significant in predicting increased marital satisfaction.
Keywords: Marriage; Financial management; Rural couples; Farm couples; Marital satisfaction; Financial Satisfaction; Economics, Agricultural (0503); Psychology, Clinical (0622); Sociology, Individual and Family Studies (0628)